Depresi dan Dukungan Sosial sebagai Determinan Kualitas Hidup Lansia di Panti Werdha - Utami, Sisca Putri; Ardian, Iwan; Luthfa, Iskim (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Depression has been shown to decrease cognitive, emotional, and physical function, thus impacting the quality of life of the elderly. Conversely, social support plays an important role as a protective factor that can reduce the risk of depression and improve the well-being of the elderly. The purpose of this study was to analyze the relationship between depression and social support with the quality of life of the elderly living in nursing homes. This study was a literature review with a search of articles from PubMed, ScienceDirect, Scopus, ProQuest, SpringerLink, and Google Scholar. The keywords used were depression, social support, quality of life, elderly, and nursing home. The selected articles were published between 2019 and 2024 with respondents from elderly in nursing homes. A total of 12 articles met the inclusion criteria and were analyzed narratively and thematically. The review results showed consistent findings that depression was significantly negatively associated with the quality of life of the elderly, with a decrease in scores of up to 30–50% in elderly with moderate-severe depression. Conversely, social support was positively associated with the quality of life, both directly and through a reduction in depressive symptoms. Emotional and family support were reported as the most influential factors. Cross-national studies show similar patterns, although the intensity of the influence varies across cultural and social contexts. These studies conclude that depression is a major risk factor for declining quality of life in older adults, while social support plays a protective role.Keywords: elderly; nursing homes; depression; social support; quality of life ABSTRAK Depresi terbukti menurunkan fungsi kognitif, emosional, dan fisik sehingga berdampak pada penurunan kualitas hidup lansia. Sebaliknya, dukungan sosial berperan penting sebagai faktor protektif yang mampu menurunkan risiko depresi sekaligus meningkatkan kesejahteraan lansia. Tujuan dari studi ini adalah untuk menganalisis hubungan antara depresi dan dukungan sosial dengan kualitas hidup lansia yang tinggal di panti werdha. Studi ini adalah telaah literature review dengan pencarian artikel dari PubMed, ScienceDirect, Scopus, ProQuest, SpringerLink, dan Google Scholar. Kata kunci yang digunakan adalah depression, social support, quality of life, elderly, dan nursing home. Artikel yang dipilih adalah publikasi 2019–2024 dengan responden lansia di panti werdha. Sebanyak 12 artikel memenuhi kriteria inklusi dan dianalisis secara naratif serta tematik. Hasil telaah menunjukkan konsistensi temuan bahwa depresi berhubungan negatif signifikan dengan kualitas hidup lansia, dengan penurunan skor hingga 30–50% pada lansia dengan depresi sedang-berat. Sebaliknya, dukungan sosial berhubungan positif dengan kualitas hidup, baik secara langsung maupun melalui penurunan gejala depresi. Dukungan emosional dan keluarga dilaporkan sebagai faktor paling berpengaruh. Studi lintas negara menunjukkan pola yang serupa, meskipun intensitas pengaruh bervariasi sesuai konteks budaya dan sosial. Studi ini menyimpulkan bahwa depresi menjadi faktor risiko utama penurunan kualitas hidup lansia, sementara dukungan sosial berperan sebagai faktor protektif.Kata kunci: lansia; panti werdha; depresi; dukungan sosial; kualitas hidup